2011
DOI: 10.4236/jct.2011.21003
|View full text |Cite
|
Sign up to set email alerts
|

Case of Advanced Recurrent Glioblastoma Successfully Treated with Monoterpene Perillyl Alcohol by Intranasal Administration

Abstract: We report a case of recurrent glioblastoma (GBM) successfully treated with the Ras inhibitor monoterpene perillyl alcohol by intranasal administration. A 37-years-old white woman had been previously submitted to three neurosurgical procedures, in June 2000 for radical tumor excision of grade II astrocytoma; in July 2003 for first recurrence of type IV glioma and in August 2004 for GBM recurrence. After last surgery, patient started a new cycle of chemotherapy but was refractory to treatment, presented clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
(35 reference statements)
1
5
0
1
Order By: Relevance
“…This is consistent with previous findings that patients with deep gray matter glioma may survive longer than those with tumors in a lobar location (Ramnarayan et al, 2007). The present results partly explain previous data (da Fonseca et al, 2011) showing that tumor location and polymorphisms of GSTM1 and GSTT1 may exert additional influence on the survival of patients with malignant gliomas. It is important to conduct larger studies to confirm whether GST genotypes that encode high-activity enzymes influence POH detoxification, which may be an independent predictor of outcome and response to POH-based therapy.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous findings that patients with deep gray matter glioma may survive longer than those with tumors in a lobar location (Ramnarayan et al, 2007). The present results partly explain previous data (da Fonseca et al, 2011) showing that tumor location and polymorphisms of GSTM1 and GSTT1 may exert additional influence on the survival of patients with malignant gliomas. It is important to conduct larger studies to confirm whether GST genotypes that encode high-activity enzymes influence POH detoxification, which may be an independent predictor of outcome and response to POH-based therapy.…”
Section: Discussionsupporting
confidence: 93%
“…The main advantage of the IN route is the chance of reduced side effects in other organ systems [146,154]. Different approaches showed that chemotherapeutic agents for treating brain tumours such as perillyl alcohol, methotrexate and telomerase inhibitors can be delivered via the nasal route and are effective alternative strategies [155][156][157][158][159][160].…”
Section: Intranasal Application Used For Cns Deliverymentioning
confidence: 99%
“…One reason is that these monoterpenes, when administered orally, are characterized by holding relatively insufficient ‘druglikeness’, This comes about because these metabolites are poorly soluble in water due to their lipophilic nature, hence, issues arise in their transportation within the blood system. However, monoterpenes can easily be administered intranasally, as has been proven clinically useful in the treatment of recurrent glioblastoma . In this review, particular attention will be paid to the influence of monoterpene structure on their physicochemical properties and pharmacological activity.…”
Section: Introductionmentioning
confidence: 99%